2000
DOI: 10.1006/dbio.1999.9587
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchyme with fgf-10 Expression Is Responsible for Regenerative Capacity in Xenopus Limb Buds

Abstract: A young tadpole of an anuran amphibian can completely regenerate an amputated limb, and it exhibits an ontogenetic decline in the ability to regenerate its limbs. However, whether mesenchymal or epidermal tissue is responsible for this decrease of the capacity remains unclear. Moreover, little is known about the molecular interactions between these two tissues during regeneration. The results of this study showed that fgf-10 expression in the limb mesenchymal cells clearly corresponds to the regenerative capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(71 citation statements)
references
References 44 publications
1
70
0
Order By: Relevance
“…The importance for Fgf signalling has also been functionally demonstrated for limb regeneration. A correlation between Fgf-10 expression in the limb bud mesenchyme and the ability to regenerate has been observed (Yokoyama et al, 2000) and a gain-offunction approach showed that Fgf-10 is indeed responsible for the regenera-tive capacity . Beads soaked in recombinant Fgf-10 protein and then placed in the stump of a nonregenerative limb (st. 56) were able to restore some regenerative capacity to the limb ).…”
Section: Fgf Signalingmentioning
confidence: 97%
See 2 more Smart Citations
“…The importance for Fgf signalling has also been functionally demonstrated for limb regeneration. A correlation between Fgf-10 expression in the limb bud mesenchyme and the ability to regenerate has been observed (Yokoyama et al, 2000) and a gain-offunction approach showed that Fgf-10 is indeed responsible for the regenera-tive capacity . Beads soaked in recombinant Fgf-10 protein and then placed in the stump of a nonregenerative limb (st. 56) were able to restore some regenerative capacity to the limb ).…”
Section: Fgf Signalingmentioning
confidence: 97%
“…To determine whether the mesenchyme or the epidermis was responsible for the decline in regeneration success, Yokoyama et al created recombinant limbs, combining mesenchyme and epidermis from regeneration competent (st. 52) and incompetent (st. 56) limbs (Yokoyama et al, 2000). The regenerative mesenchyme was able to induce fgf-8 expression in the regenerative incompetent epidermis and as a consequence, regeneration could proceed.…”
Section: Box 2: Variation In Regenerative Success Of Tadpole Hindlimbsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yokoyama et al. (2000) demonstrated that mesenchymal Fgf10 maintains Fgf8 expression by the AEC in regenerating Xenopus limb buds, and vice versa. Xenopus limbs lose the power of regeneration as they differentiate and form a blastema of fibroblast‐like cells (Dent, 1962; Van Stone, 1964).…”
Section: Blastema Growthmentioning
confidence: 99%
“…Xenopus limbs lose the power of regeneration as they differentiate and form a blastema of fibroblast‐like cells (Dent, 1962; Van Stone, 1964). This loss is accompanied by a loss of Fgf10 expression by the fibroblastema and loss of Fgf8 expression by the AEC (Yokoyama et al., 2000) due to changes in the limb bud cells related to their differentiation (Filoni, Bernardini, & Cannata, 1991; Sessions & Bryant, 1988). Fgf10‐soaked beads placed on the amputation surface of regeneration‐deficient limbs of Xenopus late tadpoles restore Fgf8 expression in the AEC and digit regeneration, although not more proximal structures (Yokoyama, Ide, & Tamura, 2001).…”
Section: Blastema Growthmentioning
confidence: 99%